PENGARUH KUALITAS KERJA DAN MOTIVASI KERJA TERHADAP SEMANGAT KERJA (Studi Pada Petugas Kebersihan pada RSUD Dr. Fauziah Bireuen) - Marjuli, Eri; Wahyuni, Sribudi; Herlina, Herlina (JURNAL KEBANGSAAN, 2023)
This study aims to examine the effect of work quality and work motivation on morale. The study was conducted at RSUD dr. Fauziah Bireuen. The sample of this study was 51 hospital cleaners. Data analysis used multiple linear regression with the help of SPSS software. The results showed that work quality had a partial effect on the work morale of cleaners. Work motivation also had a partial effect on work morale. Both work quality and work motivation had a simultaneous and significant effect on the work morale of cleaners at RSUD dr. Fauziah Bireuen. The correlation coefficient (R) of 0.740 indicates a very strong relationship between the independent variable and the dependent variable. And with a determination coefficient of 54.8%, variations in work morale are explained by work quality and motivation.